REAKSI PENATAAN ULANG FRIES PADA EUGENIL ASETAT - kusmiyati kusmiyati; Sabirin Matsjeh; Jumina Jumina (Universitas Ahmad Dahlan, 2011)
Fries Rearrangement of eugenyl acetate in order to study allilic substituentgroup influence has been done. Fries rearrangement of eugenyl acetate was done byheating at 120°C for 3 hours under AlCl3, dichloromethane as the catalyst and solvent,respectively. The structure of the compound was identified using Infra Redspectrometry (IR) and GC-MS. The result of te research showed that rearrangementfries of eugenyl acetate are not formed, but yielded lightly brown oil of dimmer.